Prebiotic chemistry and origin of living beings: current state, scientific perspectives and (bio)ethical issues - Siqueira-Batista, Rodrigo; Alves-Ferreira, Ricardo; Maroca-de-Avelar, Rafaela Lacerda Pedra; Mayrink, Maria Isabel Cristina Batista; Silva, Eugênio; Gómez, Felipe (Frontiers in Astronomy and Space Sciences, 2026)
Throughout the 20th and 21st centuries, studies into prebiotic chemistry have made a decisive contribution to research into the origins of life. This is the theme of this article, conceived as an integrative bibliographic review, carried out by consulting descriptors in DeCS (https://decs.bvsalud.org/) and MeSH (https://www.ncbi.nlm.nih.gov/mesh/), which enabled the design of the search strategies used to retrieve articles in PubMed (https://pubmed.ncbi.nlm.nih.gov/) and SciELo (https://scielo.org/). After the article selection process, 45 texts were chosen and used to prepare this manuscript. The information collected was organized into six sections – (i) Primordial chemistry of the Earth; (ii) First organic compounds; (iii) Prebiotic chemical structures; (iv) Original living beings; (v) Scientific perspectives; and (vi) (bio)ethical implications–in which the main results and respective discussions were gathered. It is important to highlight the long road that has been traveled towards a better understanding of the events that culminated in the origins of life. The link between science and ethics in this process is essential as a prerequisite for building responsible knowledge that considers the value of all forms of existence.